Cholesterol pericarditis. A specific but rare cause of pericardial disease - Fernandes,Fábio (2001)
During a diagnostic investigation in a 40-year-old male with pericardial effusion associated with hypothyroidism, cholesterol pericarditis was detected. We report a brief review on the etiopathogeny, clinical findings, and therapeutical possibilities of this entity.